A Critical Evaluation of Vitamin D - Basic Overview 2017
DOI: 10.5772/64502
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Female Reproduction

Abstract: Vitamin D deficiency has an impact on the reproduction of more than 40% of reproductive age women globally. Fibroids are more common among African-American females owing to their decreased milk consumption and reduced absorption of ultraviolet rays, supporting the relation between vitamin D deficiency and fibroid development. Vitamin D has an inhibitory effect on leiomyoma cells by suppression of proliferation cell nuclear antigen (PCNA), BCL-2, BCL-w, CDK1, and catechol-Omethyltransferase (COMT) protein level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…AMH is produced by growing follicles, and its excess excretion is linked to PCOS. Therefore, it seems likely that vitamin D supplementation can affect ovarian function and alleviate PCOS [ 44 ]. A clinical trial reported that vitamin D supplementation in PCOS women with vitamin D deficiency was related to lower levels of AMH [ 45 ].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…AMH is produced by growing follicles, and its excess excretion is linked to PCOS. Therefore, it seems likely that vitamin D supplementation can affect ovarian function and alleviate PCOS [ 44 ]. A clinical trial reported that vitamin D supplementation in PCOS women with vitamin D deficiency was related to lower levels of AMH [ 45 ].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…Deficiency in vitamin D leads to an inability to form normal mature eggs, which in turn leads to abnormal reproductive hormonal level and ultimately infertility [10] . Initially, the construction female workers showed a low level of serum 25OH Vitamin D. After supplementation of antioxidant multivitamin capsule they showed a significant rise in the progesterone: estrogen ratio and Vitamin D level in serum.…”
Section: Umol/litmentioning
confidence: 99%
“…Among nutrients, vitamins are the most known elements essential for human health. Our body needs only tiny amounts of vitamins; however, they have a big role in maintaining a healthy status, while the deficiencies of different vitamins can harm health in different ways [5][6][7].…”
mentioning
confidence: 99%